2016
DOI: 10.1523/jneurosci.1720-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Npas1+Pallidal Neurons Target Striatal Projection Neurons

Abstract: Compelling evidence demonstrates that the external globus pallidus (GPe) plays a key role in processing sensorimotor information. An anatomical projection from the GPe to the dorsal striatum has been described for decades. However, the cellular target and functional impact of this projection remain unknown. Using cell-specific transgenic mice, modern monosynaptic tracing techniques, and optogenetics-based mapping, we discovered that GPe neurons provide inhibitory inputs to direct and indirect pathway striatal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
138
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(154 citation statements)
references
References 160 publications
13
138
2
1
Order By: Relevance
“…TI neurons are also included which, in contrast to TA project to STN, receive input from striatum, and where one out of every tenth TI neuron projects back to striatum. Specifically, in the striatum, TA neurons project to both MSNs and FSNs, whereas TI neurons project only to FSNs in accordance with the literature (Glajch et al, 2016; Saunders et al, 2016). …”
Section: Methodssupporting
confidence: 87%
See 3 more Smart Citations
“…TI neurons are also included which, in contrast to TA project to STN, receive input from striatum, and where one out of every tenth TI neuron projects back to striatum. Specifically, in the striatum, TA neurons project to both MSNs and FSNs, whereas TI neurons project only to FSNs in accordance with the literature (Glajch et al, 2016; Saunders et al, 2016). …”
Section: Methodssupporting
confidence: 87%
“…Experiments suggest that both TA and TI neurons connect to FSNs, whereas only TA neurons connect to MSNs (Mallet et al 2012; Smith et al, 1998; Glajch et al 2016; Saunders et al 2016). Specifically, Glajch et al (2016) showed, by light stimulation of GPe axons going to striatum, that the inhibitory postsynaptic currents (IPSCs) in FSNs were considerable larger than the IPSCs in MSN D1 and MSN D2 (600 vs. 60 and 134 pA), and Saunders et al (2016) measured IPSCs in FSNs by light stimulation of axons from TI neurons and observed large IPSCs in FSNs (437 pA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…TTX in S1 blocked most of the contralateral whisker responses and we did not identify an early thalamic component that acted as a “shortcut” preceding the cortical input, however, the properties of thalamostriatal inputs remain to be elucidated in the awake animal, aided by molecular differentiation of the respective excitatory inputs. Striatal neurons were shown to receive inputs from various presynaptic structures in the cortex, thalamus, as well as other subcortical structures in the brainstem and within the basal ganglia (Mallet et al 2012; Wall et al 2013; Dautan et al 2014; Glajch et al 2016). These pathways to striatal neurons may play a role in mediating the compound delayed responses to whisker stimulation via parallel polysynaptic pathways but are beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 99%